Individual Baseline Performance and Electrode Montage Impact on the Effects of Anodal tDCS Over the Left Dorsolateral Prefrontal Cortex - Splittgerber, Maike; Salvador, Ricardo; Brauer, Hannah; Breitling-Ziegler, Carolin; Prehn-Kristensen, Alexander; Krauel, Kerstin; Nowak, Rafal; Ruffini, Giulio; Moliadze, Vera; Siniatchkin, Michael (Frontiers in Human Neuroscience, 2020)
Anodal transcranial direct current stimulation (tDCS), applied over the left dorsolateral prefrontal cortex (lDLPFC), can produce significant effects on working memory (WM) performance and associated neurophysiological activity. However, results from previous studies are inconsistent and occasionally contradictory. This inconsistency may be attributed to methodological and individual differences during experiments. This study therefore investigated two hypotheses: 1) A multi-channel optimized montage was expected to be more effective than a classical bipolar montage, because of increased focality. 2) The subjects were expected to benefit differently from the stimulation depending on their initial task performance. In a sham-controlled cross-over study, 24 healthy participants received bipolar, multi-channel and sham stimulation for 20 minutes in randomized order, targeting the lDLPFC while performing a 2-back WM task. After stimulation, EEG was recorded at rest and during 2-back and a non-target task (Continuous Performance Task (CPT)) performance. Bipolar and multi-channel stimulation were both well tolerated and effectively blinded. We found no effect of stimulation on behavioral performance or neuronal oscillations comparing the classical bipolar or the multi-channel montage with sham stimulation. We did, however, find an interaction between stimulation and initial task performance. For multi-channel stimulation initially low performing participants tended to improve their WM performance while initially high performing participants tended to worsen their performance compared to sham stimulation. Both tDCS montages induced changes in neural oscillatory power which correlated with baseline performance. The worse the participant's initial WM performance was, the more task related theta power was induced by multi-channel and bipolar stimulation. The same effect was observed for alpha power in the non-target task following multi-channel stimulation. Notably, we were not able to show a superiority of multi-channel stimulation compared to bipolar stimulation. Still, comparing both montages with sham stimulation, multi-channel stimulation led to stronger effects than bipolar stimulation. The current study highlights the importance of investigating different parameter with potential influence on tDCS effects in combination. Our results demonstrate how individual differences in cognitive performance and electrode montages influence effects of tDCS on neuropsychological performance. These findings support the idea of an individualized and optimized stimulation setting, potentially leading to increased tDCS effects.